From the Barrio to the Barricades: Grafiteros, Punks, and the Remapping of Urban Space - Magaña, Maurice Rafael (Social justice, 2015)
The article discusses the participation of the youth in the 2006 social movement in Oaxaca, Mexico. Topics discussed include the rise of the social movement in 2006 following the violent eviction of striking teachers, support provided by Oaxacans to the teachers and to oppose police brutality, and the participation of youth in barricades across the city.